THE EFFECT OF BOKASHI KIRINYU ON GROWTH AND YIELD OF PAPRIKA ON ALLUVIAL SOIL - lestari, Rahmidiyani, Dwi Zulfita, Ayu (Fakultas Pertanian Universitas Tanjungpura, 2019)
ABSTRACT Basically, paprika plants can be cultivated on various types of soil. One of the factors that influence the growth and development of paprika is the soil factor as a medium for growing plants. One effort that can be done to overcome the problem in alluvial soil is by adding organic matter to the soil in the form of kirinyu bocation. This study aimed to investigate the effect of bokashi kirinyu on growth and yield of paprika on alluvial soil. This research was conducted at a location on Jalan Sungai Raya Dalam. The methodology used in this study was a completely randomized design (CRD) consisting of 5 treatments, 5 replications and each treatment consisted of 4 plant samples, so that there were 100 plants. The treatment in question is : k1 = 20 ton/ha bokashi kirinyu equivalent to 400 g/polybag, k2 = 25 ton/ha bokashi kirinyu equivalent to 500 g/polybag, k3 = 30 ton/ha bokashi kirinyu equivalent to 600 g/polybag, k4 = 35 ton/ha bokashi kirinyu equivalent to 700 g/polybag, and k5 = 40 ton/ha bokashi kirinyu equivalent to 800 g/polybag. Observation variables observed were to the content of chlorophyll leaves, root volume, dry weight of plants, plant height, fruit weight, and the number of fruit. The results of diversity analysis showed that significant bocation at various doses had significant effect on root volume, plant dry weight, plant height 2 mst, 4 mst and 6 mst, number of fruit crops, plant fruit weight and no significant effect on leaf chlorophyll content. The results of this study showed that giving bokashi kirinyu at a dose of 30 ton/ha equivalent to 600 g/polybag gave the best growth and yield to paprika plants on alluvial soil. Keywords: bokashi kirinyu, paprika, alluvial soil.